Penerapan Pembelajaran Problem Based Learning Dalam Meningkatkan Kkemampuan Berpikir Kritis Siswa Kelas VIII Pada Mata Pelajaran PPKn Di SMP - Baiq, Tania Febrianti; Kurniadi, Alpian; Khaerani, Nur Atira; Afriani, Dian; Suyase, I Made (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
Education is a learning process that is held to develop the potential of the student. The aim of this study is to improve the high-level thinking ability of students of the eighth grade in Pancasila Education and Citizenship (PPKn) subjects through the application of Problem Based Learning Method. This study uses the Class Action Research method that consists of two cycles, each of which has four stages: planning, action, observation, and reflection. In the first cycle, the results showed that there were 29 out of 36 descriptors (81%) that emerged as a result of the application of Inquiry Based Learning. Although the expected variable of high-level student thinking reached 32 students (80%) out of a total of 40 students, the expected target has not been achieved. Therefore, a reflection was carried out to identify the cause of non-availability of performance indicators. Based on the reflection results, an improvement was made in the second cycle, resulting in an increase of 36 descriptors (100%) from the 36 prescribed. At the same time, students' high-level thinking ability also increased to 38 students (95%) out of a total of 40 students. Referring to the findings of this study, it can be concluded that the application of Problem Based Learning successfully improved the high-level thinking ability of students of the eighth grade in PPKn subjects.